ESTUDO ELETROCARDIOGRÁFICO E CLÍNICO DE FELINOS SUBMETIDOS À ANESTESIA DISSOCIATIVA ASSOCIADA AO CLORIDRATO DE TRAMADOL, COM OU SEM FORNECIMENTO DE OXIGÊNIOTERAPIA VIA MÁSCARA - Inajara Nakamura Hirota; Rafael Cerântola Siqueira; Tami Aime Kubota; Camila Felix Cedran; Rode Pamela Gomes; Renata dos Santos Belluci; Jorge Cardoso da Silva Filho; Rodrigo Prevedello Franco (Veterinary News, 2014)
The association of tiletamine with zolazepam (T/Z) is commonly used in dissociative anesthesia in household pets. This combination induces short-duration somatic analgesia, loss of voluntary movements and myorelaxation caused by the benzodiazepin, with stimulation of the ardiovascular system and maintenance of protective reflexes. Due to the large use of this association in elective neutering of felines and its anesthetic properties, we chose to monitorize and identify electrocardiographic (ECG) and clinical changes during the anesthetic procedure, with and without oxygen supplementation. For this study, 20 female felines were recruited. All animals were young adults, healthy, no specific breed. The subjects underwent clinical, laboratorial and electrocardiographic evaluations prior to anesthesia. Tramadol hydrochloride was given as Preanesthetic medication followed by anesthesia with T/Z. The felines were randomly assigned to either Group 1 (n=10), in which subjects received oxygen supplementation through mask during the anesthetic procedure, or Group 2 (n=10), in which subjects were not supplemented with oxygen. Heart and respiratory rates, systolic blood pressure, rectal temperature and pulse oxymetry were monitored in all subjects from both groups. We also obtained recordings of the ECG tracing and derivations for each animal which were posteriorly evaluated and interpreted. The results showed significant differences between the groups in respiratory rate (G1 = 26,8 +/- 2,1 and G2= 38,5+/- 3,2) and pulse oxymetry (G1= 97,3 +/- 2,4% and G2 = 91,2 +/- 1,1%). We also observed on the ECG recordings development of periods of intermittent right branch blockage and S-T elevation in both groups. We therefore concluded that the ECG recordings were identical in both groups despite oxygenotherapy; however, we observed an improvement in the clinical parameters in animals who received oxygen supplementation via mask.